Strategy of Rational Therapy of Acute Respiratory Infections in Patients with Comorbidity - T. A. Ruzhencova; Daria А. Khavkina; Natalia A. Meshkova; Pavel V. Chukhliaev; Alexander A. Garbuzov (Безопасность и риск фармакотерапии, 2020)
Abstract. The paper discusses specific features of acute respiratory infections (ARI) progression in patients with comorbidity. The relevance of this study is accounted for by severe progression of ARIs in this group of patients, as well as by specific considerations of combining causal treatment of infections with life-long treatment of chronic diseases.The aim of the study was to use a clinical case to substantiate an optimal treatment strategy for influenza and associated complications in a comorbid patient.Results: the analysis of the clinical case showed that an unfavourable course of ARI in the patient was due to the lack of timely antiviral therapy, adverse effects of paracetamol during statin therapy, exposure to pneumonia pathogen degradation products, general intoxication, and immune response. The compromised medical history contributed to the development of severe complications. The paper proposes a strategy for selecting the most eff ective and safe approach to the treatment of ARIs in a comorbid patient.Conclusions: ARIs in patients with chronic diseases entail increased risks of complications that may arise both due to specific characteristics of the infection and unfavourable combination of drugs. Treatment regimens for infl uenza and other ARIs in comorbid patients should be eff ective and timely. Early antiviral treatment is especially important in patients with comorbidity. When choosing a treatment regimen, it is necessary to assess potential benefi ts of pharmacotherapy as well as associated risks, including those related to previously prescribed medicines.